A theoretical and empirical framework for the examination of the relationship between political instability and tourism, with special reference to selected Mediterranean … - Theocharous, Antonis L. (My University, 2002)
British Library EThOS: A theoretical and empirical framework for the examination of the relationship between political instability and tourism, with special reference to selected Mediterranean destinations New search | Advanced search | Search results Login / Register | About | Help | FAQ | Follow dividing line Use this URL to cite or link to this record in EThOS: https://ethos.bl.uk/OrderDetails.do?uin=uk.bl.ethos.268565 Title: A theoretical and empirical framework for the examination of the relationship between political instability and tourism, with special reference to selected Mediterranean destinations Author: Theocharous, Antonis. ISNI: 0000 0001 3516 7829 Awarding Body: University of Sunderland Current Institution: University of Sunderland Date of Award: 2002 Availability of Full Text: Access from EThOS: Order from print (fee paid by institution). Please login to continue. Abstract: No abstract available Supervisor: …
Keywords: Management & business studies